Depth from Moving Apertures - Sayar, Mahmut Salih; Akgul, Yusuf Sinan (Springer, 2013)
Two new focus measure operators for Shape From Focus to estimate the three-dimensional shape of a surface are proposed in this paper. The images are formed by a camera using moving apertures. The well-focused image pixels are identified by frequency analysis or matching with the all-focused image of the scene. Frequency analysis involves the usage of classical focus measure operators and summing up for each aperture to find the focus quality to be maximized. The lesser method uses the match-points and error ratios of any matching algorithm used within an all-focused image region and all same-focus-different-aperture images to find the total displacement. The inverse of total displacement can be used as a focus quality measure. The experiments on real images show that the introduced ideas work effectively and efficiently.
28th International Symposium on Computer and Information Sciences (ISCIS) -- OCT 28-29, 2013 -- Inst Henri Poincare, Paris, FRANCE
Keywords: Defocus; Stereo